Beyond Profit: A Pedagogical Model for Integrating Philosophy into Economic Education for Value-Based Entrepreneurship in Indonesia - Nailariza Umami; Heri Pratikto; Agung Winarno (Enigma in Education, 2024)
This study addresses the imperative to cultivate a generation of entrepreneurs in Indonesia who prioritize not just profit, but also ethical conduct, social responsibility, and sustainable practices. It investigates how integrating philosophical principles into economic education can foster these values in Indonesia's youth. Employing a qualitative research design, this study critically analyzes relevant literature on philosophy, economics, and education, along with Indonesian policy documents related to entrepreneurship and economic development. The study draws upon the works of influential thinkers, adapting their ideas to the Indonesian context. The findings highlight the need for a more holistic approach to entrepreneurship education that moves beyond a narrow focus on profit maximization. Key philosophical concepts identified include ethical decision-making, social responsibility, and long-term sustainability. In conclusion, based on these findings, a pedagogical model is proposed that emphasizes active learning strategies, case studies, and community engagement to foster critical thinking and ethical decision-making among future entrepreneurs. This research contributes to the ongoing discourse on entrepreneurship education by advocating for an approach that balances economic success with societal well-being.